2011
DOI: 10.1068/p6941
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Speech in Noise: Seeing a Loud Talker is Better

Abstract: Seeing the talker improves the intelligibility of speech degraded by noise (a visual speech benefit). Given that talkers exaggerate spoken articulation in noise, this set of two experiments examined whether the visual speech benefit was greater for speech produced in noise than in quiet. We first examined the extent to which spoken articulation was exaggerated in noise by measuring the motion of face markers as four people uttered 10 sentences either in quiet or in babble-speech noise (these renditions were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 21 publications
(17 reference statements)
1
17
0
Order By: Relevance
“…For instance, talkers adapt visual elements of speech produced in noise such that articulated movements are larger and more correlated with speech acoustics, resulting in an increased perceptual benefit from visible speech (Kim et al, 2011). These adaptations occur automatically in noise but are also part of explicit communicative strategies (Garnier et al, 2010; Hazan and Baker, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, talkers adapt visual elements of speech produced in noise such that articulated movements are larger and more correlated with speech acoustics, resulting in an increased perceptual benefit from visible speech (Kim et al, 2011). These adaptations occur automatically in noise but are also part of explicit communicative strategies (Garnier et al, 2010; Hazan and Baker, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Lombard speech is one of a suite of acoustic and phonetic modification techniques; these modifications include increases in fundamental frequency (F0) and speech levels, shifted first and second frequencies, increases in higher-frequency energy, and a flattened spectral tilt. At the phonetic level, Lombard speech is characterised by increased vowel duration as well as energy shifts among different classes of phonemes [55][56][57][58][59][60][61][62][63][64][65][66][67][68]. Visually, Lombard speech is characterised by greater global movement of the jaw as well as lip spreading, opening, closing, and protrusion [69,70].…”
Section: Discussionmentioning
confidence: 99%
“…Only relatively recently has it been demonstrated that seeing the exaggerated visible articulation of speech produced in noise (Lombard speech) enables better perception of auditory speech in noise, when compared to the visible articulation of quite speech (Kim, Sironic & Davis, 2011). The Alghamdi et al's paper (this issue) investigated the impact of artificially exaggerating the visual articulatory features (the mouth kinematics) on the benefit to speech recognition performance of seeing the talker.…”
Section: Auditory Visual Speech Perceptionmentioning
confidence: 99%